Tumor grade-related thallium-201 uptake in chondrosarcomas - MANİSALI, METİN; Kaya, G. Capa; Demir, Y.; Ozkal, S.; Sengoz, T.; Manisali, METİN; Baran, O.; Koc, M.; Tuna, B.; Ozaksoy, D.; Havitcioglu, H. (My University, 2010)
Diagnosis of low-grade chondrosarcoma, especially discrimination between enchondroma and low-grade chondrosarcoma, may be difficult pathologically. The aim of this study was to evaluate the value of thallium-201 (Tl-201) scintigraphy in the diagnosis of chondrosarcoma and to investigate whether there was a correlation between Tl-201 uptake and tumor grade.